Hydrogen effects on AlGaN/GaN MISFET with LPCVD-SiNx gate dielectric. (18th February 2019) - He, Zhiyuan; Chen, Yiqiang; He, Jiang; Su, Wei; Fang, Wenxiao; En, Yunfei; Huang, Yun; Liu, Yang
Abstract: In this work, the effects of hydrogen on an AlGaN/GaN metal insulator semiconductor field effect transistor (MISFET) with SiNx gate dielectric were investigated. It is found that after hydrogen exposure, (1) the AlGaN/GaN MISFET exhibits better DC performance with larger maximum transconductance, (2) the gate lag phenomenon is effectively suppressed and (3) the 1/ f noise performance is improved with lower noise magnitude. These results are different from previous observations in other III–V semiconductor devices. Based on the theoretical analysis by space charge limited current and low-frequency noise models, we propose that the hydrogen treatment induces hydrogen incorporation into SiNx, which could passivate the defect centers. These findings demonstrate the high hydrogen tolerance of AlGaN/GaN MISFETs.